Occupational identity and police officers’ social relations in Ibadan City, Nigeria - Ojedokun, Usman Adekunle (Policing and society, 2024)
Despite the abundance of studies on the public perception of the Nigeria Police Force and the policing operations of officials of the law enforcement agency, there is a paucity of empirical research on the life and lived experiences of police officers as it concerns their occupational identity. Thus, this study investigated the impact of occupational identity on the social relations of police officers in Ibadan City, Nigeria. Symbolic interactionism theory guided the research, while data were elicited from serving and retired police officers through the combination of in-depth interview, key informant interview and focus group discussion methods. All the respondents affirmed that their work-related experiences in Nigeria over the years have consistently shown that most members of the society typically attached negativity to the police occupation. Nevertheless, there was a consensus amongst them that their involvement in police occupation conferred on them certain benefits in society. Respondents recognised the negative impact of their occupational identity on their social relations and were adopting different measures to mitigate it. There is a need for the leadership of the Nigeria Police Force in collaboration with the Police Community Relations Committee (PCRC) to design a functional roadmap through which the existing police-public gap can be systematically bridged by periodically organising public outreach and social programmes that will be strategically tailored towards systematically bringing together police officials and members of the public in a relaxed non-professional setting.